A vida do ser no mundo como potência criadora: possibilidades para o ensino de Ciências - Peixoto, Jade Cristina Corrêa (2021)
The research that resulted in this dissertation aims to understand the theoretical foundations about life as a potency of creative existence in the child as a being of the world, knowing the scientific conceptions about Life for research and teaching of sciences centered on the protagonism of the student. To this end, a bibliographic and qualitative study was carried out, initially on authors who contributed to the contextualization of the theme Life, such as Coutinho, Portocarrero, Canguilhem and Bergson. It was sought in theses and dissertations selected from research in the database of Capes (Coordination for the Improvement of Higher Education Personnel) to know a section of the productions in recent years on the theme Life and Evolution and on the authors Merleau-Ponty and Feyerabend, conducting a study using the state of the art. As well as, contributions were researched mainly by authors such as: MerleauPonty when dealing with reflections on the child as being in the world in a phenomenological perspective that values the body in its entirety associated with the perceptions of experiences with the world; Paul Feyerabend who emphasizes the plurality that permeates methods, epistemologies and cultures, thus stipulating a closed science and disassociated from people's ways of life contributes to many students not being interested in the teaching and learning of sciences because it is approached in an unbounded way their lives; Baruch Spinoza collaborates in this research by thinking about life mediated by good encounters that lead to the increase or expansion of the potency of existing, thus having more possibility of creation and invention, he also highlights the relationship of composition between body and mind, because everything that it affects the body, the mind transforms into ideas and in parallel these ideas will also directly affect the body. In addition to these authors, works by scholars such as Machado, Bicudo, Deleuze and articles referring to the main approaches of the authors were used. Therefore, there is a profound contribution from the philosophy of science, because thinking about life as a power of creative existence of the being in the world for the teaching of sciences made it possible to understand that life is beyond a list of organic properties, but it also comprises countless relationships with the world and with others, from these relationships and encounters beings are affected by joys and sorrows that lead to continuous variations in potency, knowing that teaching needs to relate to students so that their bodies are affected by joys and their powers can expand to freedom of creation. Keywords: Life, being in the world, potency to exist, science teaching, philosophy of science.